Mechanisms of and mitigating strategies for cellular immune responses to CRISPR-associated nucleases in genome editing therapy - Bryan Hu; Venkata Sumanth Reddy Gutty; Roland W. Herzog; Dongsheng Duan (Frontiers in Medicine, 2026)
Immunogenicity of CRISPR-associated nucleases (Cas) is a critical barrier to the development of safe and effective genome editing therapies. These proteins inherently pose a risk of immune recognition due to their prokaryotic origins. A multitude of factors, such as the delivery vehicle, the route of administration, components of the therapeutics, tissue microenvironment, and pre-existing immunity, also contribute to the complexity of the host immune response to Cas proteins. As CRISPR-based therapies advance into clinical settings, it is imperative to elucidate and address the immunogenicity of Cas proteins. Here, using Cas9 as an example, we review the current understanding of Cas protein immunogenicity, the challenges it poses for therapeutic application, and strategies to mitigate cellular immune responses to Cas proteins.